Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Mindfulness Therapy on Craving in Methamphetamine-Addicted Patients - Badiee, Sima; Tizdast, Taher; Ahadi, Hasan (Health Nexus, 2025)
The present study aimed to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) and Mindfulness Therapy on the craving of methamphetamine-addicted patients. The research method was quasi-experimental with a pretest-posttest control group design and a follow-up period (three months). The statistical population included all addicts who referred to addiction treatment clinics in Tehran from August to February 2021. A total of 45 participants were selected through purposive sampling and were randomly assigned to two experimental groups and one control group. The research instrument was the Craving Beliefs Questionnaire by Wright et al. (1993). The interventions, based on Free's CBT protocol (2008) and Kraft and Williams' mindfulness therapy protocol (2012), were administered over eight sessions to the experimental groups, while the control group did not receive any intervention. Data were analyzed using repeated measures ANOVA. The findings indicated a significant difference between the groups in posttest and follow-up regarding the craving of methamphetamine-addicted patients (P